Entre o fazer artístico e o contexto político: a história das histórias em quadrinhos em jornais de Caxias do Sul (1951-2000) - Menegotto, Roberto Rossi (My University, 2021)
This thesis investigates the publishing of comics on Caxias do Sul's newspapers, between 1951 and 2000, with the intention to contribute with the studies of the relation of socioeconomic themed comics and the Brazilian historic process. Initially, from the conceptualization of New Cultural History, History of the Present and Public History, as well as a short history of comics, it is made a mapping of the printing of comics on the town's newspapers, from the first one, in 1951, to the end of 2000. After that, the corpus's analysis is done, dividing into three categories: socioeconomic themed narratives related to worldwide events; socioeconomic themed narratives related to Brazilian happenings; and socioeconomic themed narratives related to Rio Grande do Sul. For this purpose, connections are established between the historical, the social and the cultural contexts of the highlighted comics and the newspapers on which they were published, in order to verify the how these narratives approach the historical events of the period. The theoretical basis is multidisciplinary, including Literary Studies, History, Sociology, Social Communication and Visual Arts. From the results, one can considerer that, based on cultural approached historical methods, comics are capable of revealing the History of a cultural space, like Caxias do Sul's. Furthermore, taken as cultural practices, comics act as representations of reality, being able to manifest the perception that participants of said space make of the actuality. [resumo fornecido pelo autor]
A presente tese investiga a publicação de histórias em quadrinhos em jornais de Caxias do Sul, entre 1951 e 2000, com vistas a contribuir para o estudo sobre a relação entre HQs de temática socioeconômica e o processo histórico brasileiro. Inicialmente, a partir da conceituação de História Cultural, História do Tempo Presente e História Pública, bem como de um breve panorama da história das histórias em quadrinhos, realiza-se um mapeamento da impressão de HQs nos jornais do município, desde a inicial, em 1951, até o final do ano 2000. Após, é executada a análise do corpus levantado em três categorias: narrativas com temática socioeconômica referentes a eventos de escala mundial; histórias com temática socioeconômica relativas a acontecimentos brasileiros; e histórias em quadrinhos com temática socioeconômica relacionadas ao Rio Grande do Sul. Para tanto, busca-se estabelecer relações entre o contexto histórico, social e cultural das HQs destacadas e os jornais em que foram publicadas, a fim de verificar a forma como essas narrativas abordaram os eventos históricos do período. O aporte teórico é multidisciplinar, contemplando Estudos Literários, História, Sociologia, Comunicação Social e Artes Visuais. Os resultados obtidos permitem considerar que, por meio de disciplinas históricas que lançam um olhar atento às manifestações culturais, as histórias em quadrinhos são capazes de revelar a História de um espaço cultural, como o de Caxias do Sul. Ademais, tomadas como práticas culturais, as HQs atuam como representações do real, passíveis de manifestar as percepções que certos participantes desse espaço fazem acerca da realidade que os rodeia. [resumo fornecido pelo autor]
Keywords: Jornais - Caxias do Sul - História; Histórias em quadrinhos; História social; Newspapers - Caxias do Sul (Brazil) - History; Comics; Social history